IMPLEMENTASI MEDIA PEMBELAJARAN GENIALLY TERHADAP MOTIVASI BELAJAR SISWA KELAS XI - Sheryl Valencia Pangaribuan; Mica Siar Meiriza (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Learning media play an important role in helping teachers create an engaging learning atmosphere and increase students’ attention during the learning process. Genially is an interactive platform that provides various creative features such as animations, quizzes, images, and interactive presentations. The implementation of Genially-assisted learning media is expected to improve students’ learning motivation so that they become more active, enthusiastic, and interested in participating in the learning process. This study aims to analyze the effect of implementing Genially learning media on students’ learning motivation. The research method used was a quantitative approach with an experimental research design. Data collection techniques were carried out through observation and documentation. The validity test results showed that all statement items were declared valid because the r-count value was greater than the r-table value of 0.329. The results of hypothesis testing also indicated a significant effect between the implementation of Genially learning media and students’ learning motivation. Thus, the implementation of Genially learning media can improve students’ learning motivation in the economics learning process. Therefore, Genially learning media is considered effective in increasing students’ learning motivation during the learning process. Keywords: Learning Media, Genially, Learning Motivation   Abstrak: Media pembelajaran memiliki peranan penting dalam membantu guru menciptakan suasana belajar yang menarik serta mampu meningkatkan perhatian siswa selama proses pembelajaran berlangsung. Genially, platform interaktif yang menyediakan berbagai fitur kreatif seperti animasi, kuis, gambar, dan presentasi interaktif. Implementasi media pembelajaran Genially diharapkan dapat menumbuhkan motivasi belajar siswa sehingga mereka lebih aktif, antusias, dan tertarik dalam mengikuti pembelajaran. Penelitian ini bertujuan untuk menganalisis pengaruh implementasi media pembelajaran Genially terhadap motivasi belajar siswa. Metode penelitian yang digunakan adalah pendekatan kuantitatif dengan jenis penelitian eksperimen. Pengumpulan data dilakukan melalui kegiatan observasi dan dokumentasi. Hasil uji validitas menunjukkan bahwa seluruh item pernyataan dinyatakan valid karena nilai r hitung > r tabel sebesar 0,329. Hasil pengujian hipotesis juga menunjukkan adanya pengaruh yang signifikan antara implementasi media pembelajaran Genially terhadap motivasi belajar siswa. Dengan demikian, implementasi media pembelajaran Genially dapat meningkatkan motivasi belajar siswa dalam proses pembelajaran ekonomi. Oleh karena itu, media pembelajaran Genially dinilai efektif digunakan untuk meningkatkan motivasi belajar siswa dalam proses pembelajaran. Kata kunci: Media Pembelajaran, Genially, Motivasi Belajar